Acceptability and feasibility of a comprehensive fall prevention model for independent older adults: A qualitative evaluation - Francisca Marquez-Doren; Camila Lucchini-Raies; Claudia Alcayaga; Claudia Bustamante; Marcela González-Agüero (Elsevier, 2024)
Background: Falls amongst the elderly represent a global public health challenge because of their potential to cause illness, death, and reduce the autonomy of this group. They also impact the emotional, family, social and economic well-being of those involved. Various strategies to prevent falls have been reported in the literature, focusing mainly on addressing individual risk factors, and on the continuous assessment of the risk of falls in older people. Objective: This study evaluated user satisfaction and acceptability of a comprehensive model, implemented in the community, to prevent falls amongst independent older adults aged 65 years and above. It sought to capture both the perceptions of the individuals who received the intervention and of the interventionists who implemented it. The study protocol was registered at ClinicalTrials.gov in November 2020 (ID: NCT04313062). Design: Qualitative, exploratory study using a case study design. The evaluation of the intervention followed the recommendations proposed by the Medical Research Council for complex interventions. Methods and participants: In the period between April 2021 to April 2022, 11 semi-structured interviews were conducted with independent older adults between 65 and 80 years of age who participated in the implementation of the comprehensive model in Santiago, Chile. Data were also collected with eight interventionists through: three semi-structured interviews at the beginning of the intervention; and two focus groups with seven interventionists at the end of the implementation of the model. The team members undertook a content analysis of the data collected. Results: Three themes emerged to account for the satisfaction and acceptability of the intervention with the model on the part of the participants and interventionists: (1) Previous experience of older persons and interventionists; (2) The older person-interventionist encounter and its context; and (3) Identification of facilitators, strengths and challenges for the implementation of the model. The results show a positive assessment of the model, highlighting the value of the social contact derived from the intervention by both participants and interventionists. Although the model involved an individual intervention, the participants' accounts indicate that it reached out to others, including family members and other elderly acquaintances. Moreover, the interventionists helped identify challenges in implementation and made recommendations to strengthen the model. Conclusion: The evaluation of satisfaction and feasibility of implementing the model showed positive results that will nurture the next phase of development of this model, which involves scaling up the intervention.